Trading legality with precaution: preliminary impacts of management plans and forest certification in the Cameroonian forests. - Cerutti, P.O.; Tacconi, L.; Nasi, Robert (Stellenbosch University, 2011)
As of mid-2008, 63 of the 101 available forest management units (FMUs) in Cameroon were managed according to approved management plans, and seven FMUs had received a FSC certification. This paper provides a preliminary assessment of the volumetric and financial variations incurred by logging companies and by the government when adopting both the management plans and the FSC regulations. The full adoption of sustainable, or at least precautionary, values into approved management plans could reduce available volumes of the most harvested species by 17%, while foregone revenues for the State could amount to about 18%. The financial losses incurred by both the State and logging companies by fully adopting improved forest management in Cameroon should deserve more attention, if viable alternative options are to be found and resistance to reform diminished.